An OER framework, heuristic and lens: Tools for understanding lecturers’ adoption of OER - Glenda Cox; Henry Trotter (Open Praxis, 2017)
This paper examines three new tools – a framework, an heuristic and a lens – for analysing lecturers’ adoption of OER in higher educational settings. Emerging from research conducted at the universities of Cape Town (UCT), Fort Hare (UFH) and South Africa (UNISA) on why lecturers adopt – or do not adopt – OER, these tools enable greater analytical insights at the institutional and cross-institutional level, and hold the potential for generic global application. The framework – the OER Adoption Pyramid – helps distinguish and compare the factors shaping lecturers’ OER adoption which are both immediate (over which they have personal control) and remote (over which they have less or no control). The heuristic – the OER Readiness Tables – derives from the Pyramid and provides a visual representation of the institutions’ obstacles and opportunities for OER engagement. The lens – of “institutional culture” – nuances these comparisons so that the analysis remains attentive to granular, idiosyncratic variables shaping OER decisions. We believe this research will have value for scholars interested in researching OER adoption, and institutions interested in promoting it.